Melatonin excretion in photoperiodic mammalian and bird species: chinchilla and Japanese quail - Dominchin, M. F. (2015)
Fil: Dominchin, M. F. Consejo Nacional de Investigaciones Científicas y Técnicas. Instituto de Investigaciones Biológicas y Tecnológicas; Argentina.